Student Satisfaction in Student Affairs and Services: Ordinary Least Squares Model Insights - Albarracin, Melanie R.; Caynila, Rhea Jane L.; Manzanades, Glazalle Marie; Segovia, Christel Kate (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This research examines the factors influencing student satisfaction with the services offered by the Office of Student Affairs and Services (OSAS) at Cebu Technological University - Argao Campus. The study gathered data from 242 students using a survey questionnaire and used Ordinary Least Squares (OLS) model analysis to measure the impact of personnel competency and professionalism, service experience and interaction, and service commitment and environmental factors on overall satisfaction. The findings emphasize the significance of having knowledgeable, competent, and compassionate staff, as they suggest that personnel competency and professionalism greatly influences student satisfaction. The result also stresses the importance of service experience and interaction, indicating that higher education institutions should prioritize being responsive to student inquiries, providing a safe campus environment, and promoting open communication with students. Additionally, the study highlights the importance of environmental factors and service commitment, arguing that improving student satisfaction requires operational enhancements such as quicker service, easy navigation, and facility maintenance. Addressing these issues could lead to higher satisfaction levels, aligning with the university's goal of creating a welcoming and engaging learning environment